Brand image’s impression on impulsive buying of healthcare products - Agung, Halim; Marta, Rustono Farady; Wang, Changsong; Amanda, Mercedes (Faculty of Communications Science, Dr. Soetomo University, 2021)
The COVID-19 pandemic is a disease outbreak that makes almost everyone unable to travel freely, especially in Indonesia. Shopee is one of the marketplaces used in this research. This study aims to analyse the impression of Shopee's brand image moderated by content marketing and its impact on impulsive buying of health products during the current pandemic. Data analysis used IBM SPSS Statistics 26 and involved 119 samples using survey methods and data collection instruments in questionnaires. The implication of this research shows that optimising content marketing techniques across various digital channels is a top priority to boost impulse buying, indirectly also improving brand image.